Dielectric/thermal characteristics of recycled borosilicate glass-filled polytetrafluoroethylene - Alhaji, Ibrahim Abubakar; Abbas, Zulkifly; Mohd Zaid, Mohd Hafiz; Zainuddin, Norhazlin; Khamis, Ahmad Mamoun; Lakin, Ismail Ibrahim (Elsevier, 2022)
Polytetrafluoroethylene (PTFE) composites filled with recycled borosilicate (rBRS) glass were fabricated for printed circuit board (PCB) substrate application. The rBRS powder prepared via a ball milling technique was dispersed in the PTFE matrix in different volume fractions (5%–25%) to produce the composites through a dry powder mixing technique. The effects of filler content on the composites' structural, dielectric, and thermal properties were examined. Scanning electron microscopy showed that rBRS filler was more dispersed in the composites at lower filler contents. The composites showed excellent microwave properties with relative permittivity of 2.31 and a loss tangent of 0.0018 at the highest filler content of 25%. The composites also revealed a good thermal property with a mean CTE of 60.54 ppm/°C at 25% filler content. Experimental data were compared with theoretical predictions. The results showed that experimental values of relative permittivity agreed with calculated values from regression analysis. It was also found that the logarithmic general mixing model gave an excellent estimate of the loss tangent of the composites.